Studi Fenomenologis-Historis Inklusifitas Dakwah Trah Adzmatkhan di Nusantara - Ahmad Hidayatullah (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) IPMAFA, 2021)
This study uses a qualitative research type with a phenomenological-historical approach to explaining the Da'wah of the Adzmatkhan breed. The result is that the noble principles are still closely held by the next generation who have a lineage continuity with the Adzmatkhan breed. Many of those who are affiliated with NU – both structurally and culturally – still maintain this principle, even when they have to face the phenomenon of the primordial glorification of some members of the Prophet's dzuriyah which is quite disturbing. Several times they had to go head to head with high tension in order to straighten this out. However, this does not make the Adzmatkhan breed which is in the same line as NU ignore their teachings to love and respect the dhuriyah of the Prophet. In this context, they do not need formal legal recognition of the lineage, because the bigger thing to fight for is Islam in the style of ahlussunnah wal Jama'ah itself.